Iodine and alkali metal alkoxides: a simple and versatile catalytic system for fully alternating polyester synthesis from phthalic anhydride and epoxides. Issue 32 (28th July 2022) - Kummari, Anjaneyulu; Pappuru, Sreenath; Singha Roy, Sourav; Chakraborty, Debashis
Abstract : Regioselective ROCOP of various epoxides with phthalic anhydride using readily available and economical catalysts i.e. I2 in combination with alkali metal alkoxides was used. Abstract : A new environmentally benign synthesis of polyesters involves ring-opening alternating copolymerization (ROAC) of phthalic anhydride (PA) with various epoxides, utilizing molecular iodine and alkali metal alkoxides as novel dual catalytic systems under solvent-free conditions. With a suitable combination of iodine and alkali metal alkoxides, the reaction can be performed to a level of >99% conversion with good regioselectivity and respectable TOF values of 16 to 50 h −1 . We examined a series of commercial alkali metal alkoxides (MeOLi/Na/K, iPrOLi/Na/K, and t BuOLi/Na/K) in combination with molecular iodine for the copolymerization of epoxides with PA. The results indicate that the sodium and potassium alkoxides in combination with iodine showed higher activity. Particularly, I2 / t BuOK showed markedly higher activity exhibiting respectable TOF values in the range of 16 to 50 h −1 towards the ROAC of PA with epoxides, which is comparable to the activity of metal-based complex catalysts. In addition, this methodology was employed for the copolymerization of PA with various epoxides such as CHO, PO, AGE, PGE, SO and t BGE. Each product exhibits a perfectly alternating sequence distribution, controlled molar mass ( M n up to 37.14 kDa), and low dispersity ( Đ up to 1.04). Therefore, in the present work a novel and simple catalytic system was developed for regioselective fabrication of polyesters with diverse structures.